Peningkatan Hasil Belajar pada Pembelajaran Tematik Terpadu dengan Model Kooperatif Numbered Heads Together (NHT) - Sari, Devita; Hamimah, Hamimah (Universitas Negeri Padang, 2022)
This study aims to determine the improvement of student learning outcomes in integrated thematic learning with the cooperative model Numbered Heads Together (NHT) in class V SD Negeri 16 Kampung Nan VI, Lubuk Sikaping District. This type of research is classroom action research using qualitative and quantitative approaches. This study was a teacher (practitioner) and 20 students. The results showed an increase in a). RPP cycle I averaged 82.15% with Good qualifications (B) increased in cycle II 92.85% with Very Good qualifications (SB), b) Implementation in the teacher aspect of cycle I averaged 82.81% with qualifications Good (B) increased in Cycle II 93.75% with very good qualifications (SB). While the implementation of the aspects of students in cycle I averaged 81.25% with good qualifications (B) increased in Cycle II 93.75% with very qualifications good (SB), c). Assessment of student learning outcomes in cycle I an average of 72.92 with sufficient qualifications (C) increased in cycle II 82.80 with good qualifications (B).